Group problem solving among community activists in a South African setting: an everyday cognition approach - Van Vlaenderen, Hilde (Rhodes University, Faculty of Humanities, Department of Psychology, 1998)
The study focuses on the everyday problem solving processes of a group of community activists in a rural setting in the Eastern Cape Province of South Africa. It aims to uncover: first, the local knowledge of the participants of the study with reference to the concepts problem and problem solving; second, the participants' group problem solving procedure; and third, the dialectical interrelation between the participants' knowledge and practice with reference to everyday group problem solving. It is contended that the mainstream cognitive approach and the cross-cultural tradition are inappropriate for the study of everyday cognitive processes. A 'situated cognition' approach, based on the notions of activity and cultural mediation, is proposed as a theoretical framework for the study. The ontological and epistemological assumptions underpinning the empirical study were derived from a scientific realist and a hermeneutical paradigm. Data for the inquiry into the local knowledge of the participants was collected through individual interviews. The data was interpreted, using the grounded theory techniques of constant comparison, coding and compiling theoretical diagrams. Data for the inquiry into the participants' group problem solving practice consisted of video-taped group problem solving processes. This data was analysed, using a multi layered process of progressively deeper interpretation, employing a reading guide technique. Analysis of the research data revealed that the participants perceived a problem as an impediment to satisfactory participation in society. Problem solving was considered as an emotive, cognitive and inter-active process, involving particular role players. This process had a certain structure, involved attitudes and actions and relied on particular resources. Successful problem solving was perceived to result in restoration of social equilibrium. The group problem solving procedure used by the participants consisted of a process of developing a common understanding and group consensus. The strategies employed in the process, the roles played by the participants, the rules adhered to by the participants and the structure underlying the process were all congruent with these aims. There was a mutually reinforcing interrelation between knowledge and practice with reference to the participants' problem solving.
Keywords: Group problem solving; Group problem solving -- South Africa; Cross-cultural studies -- Methodology; Cognition; Cross-cultural studies; Cognition -- Research